The Effect of Weed Solution Type and Concentration to Control Aphid Pests in Chrysanthemum Plants - Andriani, A. A. S. P. R.; I Gusti Made Arjana; Ida Bagus Komang Mahardika; Maria Scolastika Dede; Modesta Sriayuningsi Todo (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Among various flower varieties, chrysanthemum (Chrysanthemum sp.) is one of the most significant decorative flower commodities. Along with Aphis sp., which may do a great deal of harm, Thrips sp. pests pose a serious risk to chrysanthemums. Use of organic, non-toxic materials, such as plant-based biopesticides, is one substitute for managing Thrips sp. The purpose of this study is to ascertain which weed extract solutions, and at what doses, are most efficient at managing aphid pests on chrysanthemum plants. Two factors were included in the research design, which used a Factorial Randomized Block Design in a greenhouse setting: the type of weed extract solution and its concentration. Analysis of Variance (ANOVA) was used to examine the production data; at a 5% significant level, a Duncan or LSD test was then performed. The quality of the chrysanthemums was then compared to the Indonesian National Standard (SNI) 01-4478-1988. Aphid population, aphid mortality, flower diameter at full bloom, and percentage of flower damage (derived by dividing the number of damaged petals by the total number of observed petals) were among the observed variables. The findings showed that the chrysanthemums grown in the Ageratum conyzoides weed extract solution had the maximum growth and flower production, along with the lowest percentage of diseased leaves. Furthermore, the 300 grams/liter concentration demonstrated greater efficacy in impeding pest attacks, resulting in increased chrysanthemum development and a reduced proportion of leaf infection. For chrysanthemums to develop as best they can, the study advises applying a solution of Ageratum conyzoides weed extract at a dosage of 300 grams/liter.